The homeobox protein VentX reverts immune suppression in the tumor microenvironment - Yi Le (Nature Portfolio, 2018)
Tumour associated macrophages (TAMs) polarize into either pro-tumor or anti-tumor phenotypes. Here the authors show that the homeobox protein VentX is downregulated in clinical samples of colorectal cancer and regulates TAMs plasticity with its forced re-expression converting TAMs into an anti-tumor phenotype.